The etiology of community-acquired pneumonia among children under 5 years of age in mainland China, 2001–2015: A systematic review - Guijun Ning; Xuxia Wang; Dan Wu; Zundong Yin; Yixing Li; Huaqing Wang; Weizhong Yang (Human Vaccines & Immunotherapeutics, 2017)
Background: The aim of this systematic review was to examine the etiology of community-acquired pneumonia (CAP) among Chinese children younger than 5 y and provide evidence for further cost-effectiveness analyses for vaccine development, diagnostic strategies and empirical treatments. Methods: The literature review followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses statement. Data were obtained by searching PubMed, Embase, Web-of Science, and the Chinese databases Wanfang Data and China National Knowledge Infrastructure. All CAP etiological studies on children under 5 y of age from China published in Chinese and English between the years of 2001 and 2015 were included. A total of 48 studies were included in the final review, comprising 100 151 hospitalized children with CAP episodes. Heterogeneity and the percentage of variation between studies was analyzed based on Q statistic and I2 indices, respectively. Random effect models were used to calculate the weighted average rate in all analyses. Results: The most frequently detected bacterial agents were Klebsiella pneumoniae (5.4%), Streptococcus pneumoniae (5.2%), Escherichia coli (5.2%), Staphylococcus aureus (3.9%), Haemophilus influenza (3.6%) and Haemophilus parainfluenzae (3.3%). The most frequently detected viruses were human rhinovirus (20.3%, in just 2 studies), respiratory syncytial virus (RSV, 17.3%), human bocavirus (9.9%), parainfluenza virus (5.8%), human metapneumovirus (3.9%) and influenza (3.5%). Mycoplasma pneumoniae and Chlamydophila pneumoniae were identified in 9.5% and 2.9%, respectively, of children under 5 y of age with CAP. Conclusion: This article provides the most comprehensive analysis to date of the factors contributing to CAP in children under 5 y of age. S. pneumoniae, H. influenzae and influenza were the most common vaccine-preventable diseases in children. Corresponding, vaccines should be introduced into Chinese immunization programs, and further economic evaluations should be conducted. RSV is common in Chinese children and preventative measures could have a substantial impact on public health. These data also have major implications for diagnostic strategies and empirical treatments.